Optimum Gait Selection for Quadruped Robots - Silva, Manuel (2006)
This paper studies periodic gaits of quadruped animals and its application to multilegged artificial locomotion systems. The purpose is to determine the best set of gait and locomotion variables during walking, for different robot velocities and intrabody compliance characteristics, based on two formulated performance measures. A set of experiments reveals the influence of the gait and locomotion variables upon the proposed indices, namely that the gait and the locomotion parameters should be adapted to the robot forward velocity and to the robot intra-body compliance characteristics.